Peningkatan Hasil Belajar Peserta Didik dengan Model Index Card Match pada Pembelajaran Pendidikan Pancasila di Kelas V SDN 05 Tarok Dipo Kota Bukittinggi - Rahmatina, Rahmatina; Noraslinda, Noraslinda (Lembaga Yasin AlSys, 2024)
This research was motivated by the low learning outcomes of students and this condition was caused by the fact that during the preparation of learning planning it was found that the attachments to the teaching modules were incomplete because they were not accompanied by learning media attachments, the eval_uation questions had not been differentiated between formative and summative, the learning activities had not been explained. which are included in the Pancasila student profile and many still use the word student which should be replaced with student. The aim of this research is to describe the improvement in student learning outcomes through the Index Card Match model in Pancasila education learning in class V at SDN 05 Tarok Dipo, Bukittinggi City. This research is classroom action research (PTK) which uses qualitative and quantitative approaches. This research was carried out in two cycles, namely cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. Each cycle includes four stages, namely planning, implementation, observation and reflection. The subjects of this research were teachers and students of class V SDN 05 Tarok Dipo with a total of 25 students. Data collection techniques include observation, tests and non-tests. The results of the research showed an increase in a) the Teaching Module in cycle I with an average of 89.3% (Good), and in cycle II 96.4% (Very Good), b) implementation of learning in the teacher aspect of cycle I with an average of 73, 6% (Fair) and cycle II 93.2%, (Very Good) while the implementation of learning aspects for students in cycle I averaged 73.6% (Fair), cycle II 93.2% (Very Good), c) Student learning outcomes in cycle I averaged 74 (Fair) and cycle II 87.9 (Good). Based on these results, it can be concluded that through the Index Card Match model, student learning outcomes in Pancasila Education lessons can improve.